(untitled) (Journal of Oriental Studies, 2025)
This article examines the influence of Enlightenment thought on the literary oeuvre of Munshi Premchand, focusing on his navigation of tradition and transformation within the socio-political context of colonial India. Premchand was a very active writer who sought out new forms and ways to use artistic language and narrative to convey the themes that inspired him. The free form of the novel, the study novel, and the factual novel – all of which are quite popular today – were essentially established by him. Being at the level of the demands of his era was one of the most crucial aspects of his creative output. The roots of realistic literature, which reflects the process of man’s awakening and is primarily linked to upbringing, conventional foundations, and beliefs and biases, were established during the national liberation fight. However, because it started during a time when the spiritual forces of the entire population were under tremendous strain, the author frequently left out crucial social, everyday, and psychological details that were crucial to the development of a person’s character. These details surfaced later, when things had calmed down and it was necessary to take a closer look at oneself and one’s surroundings. By engaging with Enlightenment ideals such as reason, individualism, and social justice, Premchand critiques traditional norms while advocating for progressive change. Through a detailed analysis of key works, including Godan, Nirmala, and Kafan, the study highlights how Premchand’s narratives reflect the struggles of individuals grappling with the shifting dynamics of modernity. This exploration underscores Premchand’s significance in Indian literature as a bridge between cultural heritage and modern thought, revealing the enduring relevance of his insights in contemporary discussions about identity and social reform. Keywords: Enlightenment, novel, modern novel, Premchand, realism, humanism, society, literature.